LEGAL PROTECTION RIGHTS SOCIETY IN PERDA-PERDA SPATIAL PLANNING AREA SE-NTB - Arba, Arba (Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACT Spatial planning involves the various parties, one of which is public. For it is as one of the interested parties, the rights and obligations of society should be organized and well protected. Therefore, this research aims to study and understand the legal protection of the rights of people in Spatial Plan (RTRW) in West Nusa Tenggara. This research is normative law, then the approach is the approach used legislation (statute approach), approaches the concept, a comparative approach and analytical. The results of study after study and analysis showed that both philosophically and legally (constitutionally) has laid the solid foundation on the protection of the rights of the community in various aspects of development. However, having researched and studied various laws and regulations RTRW NTB and RTRW District / City has not been set up and protect the rights of the community well, the peoples rights are still ignored by the government. Therefore, the government must be willing and encouraged to re-evaluate.